Monitoring of theoretical knowledge on the subject "physical culture" of secondary school graduates - Makhmudov Ravshan (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article presents the results of experimental research conducted to determine the theoretical background level of graduating class students in secondary schools.